(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The work of data communication and developing software on the automation systems is related to 13 existing piston compressors located within the compressor station C144-M5 Bustuchin, Gorj, Romania. A project solution was applied to all 13 compressors and involves the communication of the parameter values of the compressors from the C144-M5 Bustuchin station to a local higher hierarchical system and a remote higher hierarchical system. The article presents the compressor automation system with a reliable architecture and a performing data communication network. The article mainly focuses on the developed software solution for the station operator panel, the compressor operator panels, and the station computer. In the second part of the article, the communication solutions for a complex data network with a higher local hierarchical system and a higher remote hierarchical system are presented from the point of view of the data server and the addresses assigned for each compressor parameter.